Kierkegaard And The Ends Of Language - Hale, Geoffrey A. (Book collections on Project MUSE., 2002)
In mutually reflective readings of Kierkegaard's foundational texts through the work of three pivotal authors-Franz Kafka, Theodor Adorno, and Rainer Maria Rilke-Hale shows how each of these writers draws attention to the unwavering sense of human finitude that pervades all of Kierkegaard's work and, with it, the profoundly unsettling indeterminacy in which it results.